2021
DOI: 10.3389/fpsyg.2021.697093
|View full text |Cite
|
Sign up to set email alerts
|

The Symphony of Team Flow in Virtual Teams. Using Artificial Intelligence for Its Recognition and Promotion

Abstract: More and more teams are collaborating virtually across the globe, and the COVID-19 pandemic has further encouraged the dissemination of virtual teamwork. However, there are challenges for virtual teams – such as reduced informal communication – with implications for team effectiveness. Team flow is a concept with high potential for promoting team effectiveness, however its measurement and promotion are challenging. Traditional team flow measurements rely on self-report questionnaires that require interrupting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 106 publications
2
5
0
Order By: Relevance
“…Also, observation methods should be created. In addition, objective measures such as behavior (Gloor et al, 2022), communication (Peifer et al, 2021), or physiological parameters (Czeszumski et al, 2022; Shehata et al, 2021) should be considered as a complement to or external criterion for questionnaires and qualitative observation methods. Subsequently, an experimental paradigm should be developed which allows for testing the propositions by manipulating variables of the structure model of the IGFT.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Also, observation methods should be created. In addition, objective measures such as behavior (Gloor et al, 2022), communication (Peifer et al, 2021), or physiological parameters (Czeszumski et al, 2022; Shehata et al, 2021) should be considered as a complement to or external criterion for questionnaires and qualitative observation methods. Subsequently, an experimental paradigm should be developed which allows for testing the propositions by manipulating variables of the structure model of the IGFT.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…A clear challenge of future flow research is to differentiate individual flow in social contexts from social flow as a social phenomenon with potentially different qualities than individual flow. A recent suggestion to differentiate flow and team flow was made by Peifer et al (2021) , suggesting that flow and team flow share the central components of individual flow, while team flow-specific components are added. In their studies, van den Hout et al (2018) bridge individual experiences of flow with collective experiences of flow.…”
Section: Discussionmentioning
confidence: 99%
“…While beyond the scope of this review, for future research, there is a need to find a common definition and operationalization of the flow concept, including a common measure of flow which is used in future research to enhance the comparability of results. The EFRN has started to fulfill this aim by agreeing on a definition of flow (see section “Introduction”), and members of the EFRN have suggested models to aggregate components of flow and team flow (e.g., van den Hout et al, 2018 ; Heutte et al, 2021 ; Peifer and Engeser, 2021 ; Peifer et al, 2021 ). The next steps will be to discuss and agree on models and respective measurements.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that the window size of 60 s and the step size of 30 were significant for each classifier. In the past, deep learning-based approaches have shown promising results in a variety of application domains such as biology, medicine, and psychology [ 8 , 12 , 13 , 14 , 15 , 42 , 61 ]. However, they are computationally expensive and also require a large number of training samples [ 62 ] to build successful models compared to traditional approaches using hand-crafted features.…”
Section: Discussionmentioning
confidence: 99%